Intra-annual Variability of CO2 Flux in the Mahanadi Estuary- A Tropical Estuarine System, India - Suchismita Pattanaik; Rajesh Kumar Sahoo; Deepty Ranjan Satapathy; Chitta Ranjan Panda; Saroj Bandhu Choudhury; Pradipta Kumar Mohapatra (Annals of Marine Science - Peertechz Publications, 2017)
The inorganic carbon dynamics and the CO2 flux of estuarine system are strongly influenced by the productivity and nutrient regime of water. This study provides full seasonal coverage of assessment of the physicochemical variables of Mahanadi estuary, mainly focusing on the carbonate system through the measurement of pH, Total Alkalinity (TA), Dissolved Inorganic Carbon (DIC), both aqueous and air fCO 2, Dissolved Oxygen (DO) and chlorophyll a (chl a). The relationship of TA and DIC were found conservative throughout the study period. The estuary was found to be over-saturated with CO2 and acted as a net source. However, the magnitude of flux varied from season to season with a range between -8.14 to 8.09 μmol m-2 h-1 indicating ephemeral sink phase in the estuary. The air-water CO2 flux was primarily governed by fCO2 (water) although other factors such as temperature, pH, salinity, total alkalinity, wind speed and fCO2 (air) noticeably affected CO2 flux. A strong positive correlation was observed between temperature and inorganic nutrients during the study period. The study of net ecosystem metabolism justifies the heterotrophic nature of Mahanadi estuarine system.